How positive affect moderates job characteristics and lecturer job satisfaction in higher Islamic education? - Zaky, Muhammad; Fithriany, Yulia; Budiman, Budi (Journal of Islamic Economics and Business, 2026)
This study examines how job characteristics dimensions and positive affect influence job satisfaction among lecturers in Faculties of Islamic Economics and Business at State Islamic Religious Universities (PTKIN) in Indonesia. It aims to address the growing concern regarding academic job satisfaction within Islamic higher education institutions facing increasing professional and institutional demands. Despite the strategic role of lecturers in ensuring educational quality, declining job satisfaction remains a persistent issue in Indonesian higher education. Limited empirical evidence exists on how job design and affective dispositions jointly influence lecturer satisfaction in Islamic university contexts.This study contributes to the literature by integrating the Job Characteristics Model and dispositional affect theory through moderation analysis in the context of Islamic higher education. It provides empirical evidence on the interactive effects between job characteristics and positive affect, which remain underexplored in prior studies. This study employed a quantitative explanatory survey design involving 207 lecturers from seven PTKIN institutions in Java. Data were collected using validated instruments and analyzed using moderated regression analysis to examine direct and interaction effects among variables. The results indicate that skill variety, task identity, task significance, and autonomy have significant positive effects on job satisfaction, while feedback does not show a significant influence. Positive affect demonstrates a consistent positive relationship with job satisfaction. Furthermore, positive affect partially moderates the relationships between most job characteristics dimensions and job satisfaction, although the moderation effects are negative. This study confirms the relevance of job design and affective dispositions in shaping lecturer job satisfaction within Islamic higher education. The findings suggest that institutional efforts should integrate job enrichment strategies with psychological well-being programs to enhance academic performance and organizational sustainability.